Vascular pericranial graft: A viable resource for frontal sinus obliteration - Morais de Melo, Willian [UNESP]; Sonoda, Celso Koogi [UNESP]; Garcia, Idelmo Rangel [UNESP] (Wolters Kluwer, 2013)
Inappropriate treatments of frontal sinus fractures may lead to serious complications, such as mucopyocele, meningitis, and brain abscess. Assessment of nasofrontal duct injury is crucial, and nasofrontal duct injury requires sinus obliteration, which is often accomplished by autologous grafts such as fat, muscle, or bone. These avascular grafts have an increased risk of resorption and infection, as well as donor site morbidity. For these reasons, pericranial flap, which is vascular, should be used for frontal sinus obliteration. The pericranial flap presented with less morbidity procedure and has decreased infection rates, which justifies its use in frontal sinus obliteration. This paper aims to report a case of a comminuted frontal sinus fracture in a 29-year-old man who was successfully treated by frontal sinus obliteration, using pericranial local flap. The patient was followed up postoperatively for 16 months without infection. Copyright © 2013 by Mutaz B. Habal, MD.
Keywords: facial fracture; Frontal sinus; galeal frontalis myofascial flap; infection; sinus obliteration; titanium plate